Testing of parameter's instability in a balanced panel: An application to real effective exchange rate for SAARC countries - Varun Agiwal; Jitendra Kumar; Sumit Kumar Sharma (Economics and Econometrics Research Institute (EERI), 2017)
Present paper considers structural break in panel AR(1) model which allows instability in mean, variance and autoregressive coefficient. This model is extension of univariate model proposed by Meligkotsiduo et al. (2004) and review of existing panel data time series model considering break studied by Levin et al. (2002), Pesaran (2004), Bai (2010), Liu et al. (2011), Wachter and Tzavalis (2012). Paper dealt the identification of structural break by comparing the posterior probability of all possible models like break on all three parameters, only two parameters, one parameter and there is no break. A simulation study is carried out to validate the derived theorems. An Empirical analysis on Real Exchange Rate of India and its neighboring countries (SAARC countries including China) are also carried out. The present study is correctly identifying the common break on 1991 which happened due to second gulf war and international debt crisis.
Keywords: C11; C12; C23; 330; Panel autoregressive model; Structural break; Prior and Posterior probability